1983
DOI: 10.1002/jez.1402250204
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the brain and the eye cooling system in birds: A morphometric analysis of the Rete ophthalmicum

Abstract: A morphometric analysis has been made of the rete ophthalmicum which is a functional arteriovenous heat exchange system in the heads of birds. The morphological data were obtained from histological sections of the rete from 40 species of birds covering a weight range of 20,000-fold. The maximal number of retial arteries, the length, the diameter of the arteries, the total arterial cross-sectional area, and the maximal exchange area have been expressed in terms of allometric equations. Other parameters importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 22 publications
3
48
0
Order By: Relevance
“…The periorbital region was chosen as this provided the only region of the body that was uninsulated and is associated with a rich intermingled network of small blood vessels, the rete ophthalmicum that can affect the heat loss from the eye 31 . The fast frame rate of the thermal videoing technique was able to show a drop in eye-region temperature of approximately 2 °C in 10 sec followed by a subsequent rise in temperature to within 0.5 °C of baseline within 3 min.…”
Section: Discussionmentioning
confidence: 99%
“…The periorbital region was chosen as this provided the only region of the body that was uninsulated and is associated with a rich intermingled network of small blood vessels, the rete ophthalmicum that can affect the heat loss from the eye 31 . The fast frame rate of the thermal videoing technique was able to show a drop in eye-region temperature of approximately 2 °C in 10 sec followed by a subsequent rise in temperature to within 0.5 °C of baseline within 3 min.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, the ophthalmic rete appears to be an analogue of the carotid rete in mammals, allowing heat to be transferred from warm arterial blood to cool venous blood returning from evaporative surfaces of the head. Blood from the two pathways is thought to mix, so that the resultant brain temperature reflects the relative contribution of blood from the each pathway (Midtgard, 1983). If arterial blood is cooled in the rete, and most of the blood supply to the brain is via this indirect pathway, selective brain cooling will be invoked.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, birds that have a poorly developed rete (zebra finch; Bech and Midtgard, 1981) or no rete (calliope hummingbird; Burgoon et al, 1987), exhibit a reduced capacity for selective brain cooling. Although the cranial blood supply in ostriches has not been systematically investigated, it has been reported that they have a welldeveloped ophthalmic rete (Midtgard, 1983), and one would predict that selective brain cooling occurs by a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is the external ophthalmic artery. On its way through the temporal fossa, the artery releases several small branches, fewer than 10 in a 10 g finch and more than 200 in a 200 g kestrel [38], that are intertwined with veins carrying cool blood returning from the moist surfaces of the nasal and buccal cavities and the eye [39,40]. Downstream from the rete, the retal arteries rejoin the external ophthalmic artery, the final destinations of which are the anterior regions of the brain and the eye.…”
Section: Birdsmentioning
confidence: 99%